Presence of Functional Neurotrophin TrkB Receptors in the Rat Superior Cervical Ganglion - Valle-Leija, Pablo; Cancino-Rodezno, Angeles; Sánchez-Tafolla, Berardo M.; Arias, Erwin; Elinos, Diana; Feria, Jessica; Zetina, María E.; Morales, Miguel A.; Cifuentes, Fredy (Frontiers in Physiology, 2017)
Sympathetic neurons express the neurotrophin receptors TrkA, p75NTR, and a non-functional truncated TrkB isoform (TrkB-Tc), but are not thought to express a functional full-length TrkB receptor (TrkB-Fl). We, and others, have demonstrated that nerve growth factor (NGF) and brain derived neurotrophic factor (BDNF) modulate synaptic transmission and synaptic plasticity in neurons of the superior cervical ganglion (SCG) of the rat. To clarify whether TrkB is expressed in sympathetic ganglia and contributes to the effects of BDNF upon sympathetic function, we characterized the presence and activity of the neurotrophin receptors expressed in the adult SCG compared with their presence in neonatal and cultured sympathetic neurons. Here, we expand our previous study regarding the immunodetection of neurotrophin receptors. Immunohistochemical analysis revealed that 19% of adult ganglionic neurons expressed TrkB-Fl immunoreactivity (IR), 82% expressed TrkA-IR, and 51% expressed p75NTR-IR; TrkB-Tc would be expressed in 36% of neurons. In addition, using Western-blotting and reverse transcriptase polymerase chain reaction (RT-PCR) analyses, we confirmed the expression of TrkB-Fl and TrkB-Tc protein and mRNA transcripts in adult SCG. Neonatal neurons expressed significantly more TrkA-IR and TrkB-Fl-IR than p75NTR-IR. Finally, the application of neurotrophin, and high frequency stimulation, induced the activation of Trk receptors and the downstream PI3-kinase (phosphatidyl inositol-3-kinase) signaling pathway, thus evoking the phosphorylation of Trk and Akt. These results demonstrate that SCG neurons express functional TrkA and TrkB-Fl receptors, which may contribute to the differential modulation of synaptic transmission and long-term synaptic plasticity.